Knowledge and information gaps implications for Philippine food security - Lapiña, Geny F. (Journal of Economics, Management & Agricultural Development, 2017)
This paper examines existing literature and data relating to food security and argues that more comprehensive database support and research programs are necessary to provide meaningful directions to address increasingly complex and interrelated issues. Knowledge about food security in the Philippines is dispersed and in some instances, scant. These are research gaps which need to be filled up because of the value of knowledge to policy formulation and comprehensive program implementation. Population growth rapid urbanization, and demographic change continue to challenge the pursuit of food and nutrition security. Similarly, the land tenure evolution, search of production possibility frontier changing demand with structural transformation, food and nutrition disconnection, climate change, and weak governance are elements of the food and nutrition security puzzle. These need to be directed toward a more cohesive and resolute approach to development. A repository of knowledge gained and gaps on the subject like a "Philippine Journal on Food Security" is a precondition worth exploring.